2017
DOI: 10.1177/0004563216686623
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width and neutrophil to lymphocyte ratio are associated with outcomes of adult subarachnoid haemorrhage patients admitted to intensive care unit

Abstract: Background Red blood cell distribution width (RDW) and neutrophil to lymphocyte ratio (NLR) have been reported to be associated with outcomes of acute cerebral infarction. However, their prognostic value in patients with subarachnoid haemorrhage (SAH) remains largely unknown. The aim of this study was to investigate the prognostic value of RDW and NLR in SAH patients. Methods Medical records of adult SAH patients admitted to intensive care unit (ICU) were extracted from Multiparameter Intelligent Monitoring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Ultimately, 31 studies with 3,487,896 patients were included in the analysis according to the inclusion and exclusion criteria (Figure 1). The characteristics of the included studies can be seen in Table 1 (4, 5, 911, 13, 2127, 2944).…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, 31 studies with 3,487,896 patients were included in the analysis according to the inclusion and exclusion criteria (Figure 1). The characteristics of the included studies can be seen in Table 1 (4, 5, 911, 13, 2127, 2944).…”
Section: Resultsmentioning
confidence: 99%
“…116 In SAH, only two retrospective studies examined NLR and found it to be associated with DCI, in-hospital death and one-year mortality. 117…”
Section: Peripheral Immune System Response In Hemorrhagic Stroke Outcmentioning
confidence: 99%
“…Similarly, the neutrophil-to-lymphocyte ratio (NLR) is an inflammatory parameter that can be easily calculated from routinely available hematology parameters [21]. Similar to RDW, NLR has been found to be a prognostic factor or diagnostic marker in various diseases, such as pregnancy-related disorders [22], thyroiditis [23], cancers [24,25], and cardiovascular diseases [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%